On the spider genus Thymoites in the Neotropical Region (Araneae, Theridiidae): nine new species, complementary descriptions and new records - Rodrigues, Everton Nei Lopes; Brescovit, Antonio D. (Zootaxa, 2015)
The theridiid genus Thymoites Keyserling, 1884 is distributed worldwide. Spiders of this genus are mainly known from the Neotropical Region, but are poorly studied in Brazil. In this paper nine new species of Thymoites are described from Brazil, one from the state of Alagoas: Thymoites murici n. sp.; two from São Paulo: T. bocaina n. sp., T. ilhabela n. sp. and T. taiobeiras n. sp. from states of Minas Gerais and São Paulo; one from the state of Santa Catarina: Thymoites tabuleiro n. sp.; and, three from state of Rio Grande do Sul: Thymoites cristal n. sp., T. camaqua n. sp. and T. piratini n. sp., all based on males and females; and one from the state of Rio de Janeiro: T. pinheiral n. sp. based on male. The male of Thymoites puer (Mello-Leitão, 1941) and the female of T. melloleitaoni (Bristowe, 1938) are here described and illustrated for the first time. Additionally, new records from Brazil are provided for Thymoites ilvan Levi, 1964 for state of Santa Catarina; T. iritus Levi, 1964 for state of Goiás; T. piarco (Levi, 1959) for state of Amazonas; and, T. struthio (Simon, 1895) for Bolivia.